Exploration of ecotypes of Achatina achatina (L) for snail farming in Ghana - Parden, Nicholas (University of Cape Coast, 2011)
Intraspecific variation in Achatina achatina achatina Linne (one of the numerous giant African snails) in Ghana was studied using chronological features, body characters and reproductive potential. Snails were collected from June to August, 2006, from four ecological regions namely Ashanti (Amansie East district), Central (Assin South district), Eastern (Suhum- Kraboa- Coaltar district) and Western (Wassa West district). In this study, the four snail populations showed a broad range of variation in size, colour pattern of shell, aestivation pattern and reproductive potential. However, electrophoresis of the haemocyanin (blood pigment) and DNA of the snails from the four ecological regions did not show any differences between them. Juvenile snails from the Western ecotype grew larger than those of the Ashanti ecotype. There was a significant difference in the aestivation pattern of the four ecotypes. Populations were characterized as distinct on the basis of shell colour, body colour, banding pattern and distribution of grey speckles on the body. The results obtained from this research indicate that the Western ecotype was more amenable to easy culture. The basis for selection of the best ecotype were growth rate, life history traits such as clutch size, hatchability of eggs, survival of hatchlings and susceptibility to harsh environmental conditions or aestivation pattern. Therefore, the Western ecotype is recommended for farming in Ghana.
xiv,133p. :ill
Keywords: snails; ecotype; Populations; farming in Ghana